Development of compliance checklist system for landed housing construction activities - Sharifah Nurul Haifa, Syed Mohd Anuar; Ezrin Hani, Sukadarin; Junaidah, Zakaria; Hanida, Abdul Aziz (IOP Publishing, 2019)
In the construction industry (landed housing), most of the accidents and near-misses in occur due to unsafe behavior of the employers and employees. Lacking compliance with regulations is also one of the causes of accidents and near-miss occurrence in the construction industry including for landed housing development). This paper aims to identify Building Operations and Works of Engineering Construction (BOWEC) requirements under Factories and Machinery Act with Regulations (Act 139), Law of Malaysia for landed housing construction activities. Behavior-Based Safety (BBS) approach is used to develop a compliance checklist based on the BOWEC requirements. The developed checklists were validated in terms of its validity by using case study in the construction industry. After the validation processes, the final checklist is ready to be used. The final checklists are divided into two parts; (1) the checklist for the employer and (2) the checklists for employees. Workplace assessment was conducted using the developed checklist. The finding reveals that more than half of the construction activities are comply with the legal requirements.